2010
DOI: 10.1016/j.cplett.2010.05.084
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoelectron spectroscopy of bulk liquids at ultra-low kinetic energy

Abstract: Time-resolved photoelectron spectroscopy (TR-PES) of ultrafast dynamics in solution is presented. To measure the photoelectron kinetic energy distribution (PKED) that is free from inelastic scattering in solution, photoelectrons were generated with ultra-low kinetic energies (ULKE: <5 eV). Time constants of the elementary processes in the charge-transfer-to-solvent (CTTS) reaction from Ito bulk water were in excellent agreement with those obtained by transient absorption spectroscopy, demonstrating the bulk-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
72
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 29 publications
8
72
1
Order By: Relevance
“…At the other end of the reaction, the prevailing view of the solvated electron is that its s-like wave function resides in a nearly spherical cavity coordinated to 4-6 water molecules 37,38 , although recent work has shown that it may extend beyond the boundaries of this cavity 39 . The early time resemblance of the TA spectra 3,5,6 to that of the aqueous electron strongly suggests that at tB0.2 ps, the structure of its first solvation shell of e À (H 2 O) is already very similar to the equilibrium one. The ejection distance upon excitation in the CTTS state at low energy was estimated to be B0.5 nm 1,9 .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…At the other end of the reaction, the prevailing view of the solvated electron is that its s-like wave function resides in a nearly spherical cavity coordinated to 4-6 water molecules 37,38 , although recent work has shown that it may extend beyond the boundaries of this cavity 39 . The early time resemblance of the TA spectra 3,5,6 to that of the aqueous electron strongly suggests that at tB0.2 ps, the structure of its first solvation shell of e À (H 2 O) is already very similar to the equilibrium one. The ejection distance upon excitation in the CTTS state at low energy was estimated to be B0.5 nm 1,9 .…”
Section: Discussionmentioning
confidence: 96%
“…The valence electrons of ground-state anions are bound by the nucleus, but the excited states are bound by solvent polarization 1 . The CTTS states of halides rapidly decay by ejection of an electron, which is then stabilized by solvation, leaving a neutral halogen atom behind [2][3][4][5][6][7][8][9][10][11][12][13][14] . Atomic anions are ideal for studies of the electron-transfer dynamics to the solvent, because the solute lacks internal (nuclear) degrees of freedom, such that the process of CTTSmediated electron ejection is entirely governed by the structure and motions of the solvation shell.…”
mentioning
confidence: 99%
See 3 more Smart Citations